Job Satisfaction of Social Service Workers in Penitentiary Institutions in Albania - Kume, Enida (European Journal of Multidisciplinary Studies, 2016)
This study analyzes job satisfaction of Social Service Workers of Penitentiary Institutions in Albania. The overall job satisfaction of Social Service Workers of Penitentiary Institutions in Albania is associated with 12 variables. These variables are the most important among all the 24 variables that taken in consideration in this study. If these factors are considered carefully, then there will be a positive overall satisfaction of Social Service Workers of Penitentiary Institutions. This study gives a message to the employers of Penitentiary Institutions that if they want to improve job satisfaction of Social Service Workers then they have to consider the above 12 variables: recognition for good work, adequate remuneration for work, feel proud of job, satisfaction from non-financial rewards, motivated to work, job is meaningful, available opportunities for promotion, exchange of ideas between superior and subordinate, job evaluated reward, relationship –colleagues, training program regularly and satisfied with available opportunities. This study covers a wide range of independent variables that significantly influences job satisfaction of Social Service Workers of Penitentiary Institutions; however, referring to the limited number of data, this study fails to bring a complete and exhaustive evaluation picture on job satisfaction of social workers of Penitentiary Institutions in Albania.
Keywords: Job satisfaction, social service workers, penitentiary institution